EVALUASI DAN DESAIN STRUKTUR SKALA UPAH DENGAN METODE OVERLAPPING DAN ADHERED DI PT XYZ - Lindawati Kartika; Nayla Shakila Fauzia; Reza Annas Tasya; Nurmalita Devi Anggraeni; Nasywa Putri Alfita; Feby Silvia; Makesha Putri Jauhar (Jurnal Pijar, 2026)
The increasing demand for effective human resource management drives organizations to establish fair and well-structured compensation systems. This study aims to analyze and compare improvements in salary structures using a salary mapping approach at PT XYZ. Data were collected from 60 employees through job analysis, payroll documentation, and interviews with management. The analysis involved job grading, salary structure design, and salary mapping evaluation to assess internal pay consistency. The findings indicate that the initial compensation structure did not fully reflect internal equity, as shown by inconsistencies between mid-to-mid and spread values across several job grades. The overlapping method resulted in a more flexible salary structure due to overlapping pay ranges between grades. In contrast, the adhered method produced a more structured system with clear salary boundaries and no overlap between job levels. Overall, the adhered method is more effective in establishing a systematic and proportional compensation structure that aligns with the company’s financial capacity.